A phase II study of the combination chemotherapy of bevacizumab and gemcitabine in women with platinum-resistant recurrent epithelial ovarian, primary peritoneal, or fallopian tube cancer - Shoji Nagao; Ai Kogiku; Kazuhiro Suzuki; Takashi Shibutani; Kasumi Yamamoto; Tomoatsu Jimi; Miho Kitai; Takaya Shiozaki; Kazuko Matsuoka; Satoshi Yamaguchi (BMC, 2020)
Abstract Introduction Bevacizumab and gemcitabine are key drugs for treating recurrent epithelial ovarian cancer. However, information about the combination of bevacizumab and gemcitabine is insufficient. We conducted a phase II study to assess the feasibility, clinical activity, and toxicity of this combination chemotherapy. Methods This study included women with platinum-resistant recurrent epithelial ovarian, primary peritoneal, or fallopian tube cancer who received one to three regimens of platinum-based chemotherapy between April 1, 2015 and December 31, 2018. The patients received bevacizumab 15 mg/kg intravenously on day 1 and gemcitabine 1000 mg/m2 intravenously on days 1 and 8 every 21 days until disease progression or unacceptable toxicity. The primary endpoint was the completion rate of three cycles of chemotherapy. This study was registered in the University Medical Information Network (UMIN) Clinical Trials Registry (UMIN000016619). Results Among the 19 patients, 18 (95%) received ≥3 and 9 (47%) received ≥6 cycles of the study therapy. The objective response rate was 42% (complete response of 16% and partial response of 26%), and the clinical control rate was 84%. Hematological toxicity included neutropenia grade 3/4 in 9 patients (47%), anemia grade 3/4 in 2 (11%), and thrombocytopenia grade 3/4 in 1 (5%). One patient (5%) had grade 3 hypertension, and 1 (5%) had grade 3 protein urea. Possibly related grade 3 pulmonary toxicity was observed in 1 patient. Three patients needed dose reduction of gemcitabine to 800 mg/m2 due to treatment delay by 15 to 21 days on day1. There was no treatment delay more than 14 days on day 8. The median progression-free survival duration was 5.1 months and median overall survival duration was 21.3 months. Conclusion The combination chemotherapy with gemcitabine and bevacizumab was feasible, effective and safe. This combination chemotherapy may be explored in a further randomized trial.